Analysis on the Psychological Effect of Interactive Integration of International Sports Organizations and Sports Tourism - Peng Ni (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This paper centres on the psychological impact of sports tourism, delineating its characteristics, connotations, and associated effects. It emphasizes that sports tourism achieves psychological outcomes among tourists through mechanisms such as diversion, moderate fatigue, physical enhancement, and character cultivation. These mechanisms underscore its significance as a crucial, civilized, and pragmatic fitness approach aimed at fostering individual well-being, longevity, and personal growth. Furthermore, it underscores the relevance of research into the psychological effects resulting from the interactive integration of sports tourism within the public domain, particularly investigations into the interplay between international sports organizations and sports tourism on public psychology. This study focuses on the integrated advancement of the sports industry and tourism within a specific province. It is discerned that the sports industry in this province exhibits a noticeable disparity compared to regions with more robust development, indicating a lack of alignment with overall economic progress, thereby necessitating expedited development efforts. Among these initiatives, integration with the tourism sector emerges as particularly pivotal. The research predominantly relies on data sourced from the China National Knowledge Network (CNKI) and relevant university library websites. A total of 380 literature resources pertaining to sports industry integration and 130 resources concerning the integration of the sports industry with tourism were gathered, alongside 60 dissertations. This paper delves into the integrated development of the sports industry and tourism within the province, revealing the existing gap between its sports industry and those of more developed provinces, highlighting the incongruity with broader economic trajectories. The confluence of sports and tourism is pronounced, facilitating reciprocal enrichment and the realization of shared benefits. Together, they foster a symbiotic relationship marked by the cultivation of a congenial milieu, the facilitation of social cohesion, and the augmentation of emotional engagement. Industrial integration, on the other hand, represents a developmental paradigm wherein diverse industries harmonize their industrial technologies, managerial practices, marketing resources, and market penetration strategies through collaborative restructuring initiatives under specific circumstances. Such endeavours transcend the constraints inherent in faltering sectors, drawing upon policy frameworks for support, leveraging cultural dynamics as a facilitative medium, and harnessing developmental imperatives while utilizing resources as conduits for advancement. The convergence of the sports and tourism industries signifies a forthcoming developmental trajectory. Market demand acts as a catalyst for integration, while resource sharing establishes the groundwork for such amalgamation. Interconnectedness and mutual reinforcement underscore the fundamental nature of fusion, with advancements in science and technology providing the requisite foundation for fusion-based technologies. The confluence of developmental pathways anticipates the potential for sustained fusion-driven progress.